2014
DOI: 10.1080/1097198x.2014.928565
|View full text |Cite
|
Sign up to set email alerts
|

Initial Adoption Versus Institutionalization of E-Procurement in Construction Firms: An Empirical Investigation in Vietnam

Abstract: This study explores the factors that impact the initial adoption and institutionalization of e-procurement in construction firms in developing countries. It proposes a research model based on an interaction perspective that is a combination of the technology-organization-environment (TOE) framework and the theory of reasoned action (TRA). Data collected from 112 construction businesses in Hanoi, Vietnam in 2012 were analyzed using partial least square-structural equation modeling (PLS-SEM). The findings show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…This finding is completely consistent with the results reported by Molla & Licker (2005). It is also supported by (Tran et al, 2014) when they found that external business characteristics were critical factors affecting the institutionalization of e-procurement in construction industry in Vietnam. They confirmed the importance of meso-level environmental factor in e-commerce adoption, as market forces tend to be relatively specific to a given sector and industry.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding is completely consistent with the results reported by Molla & Licker (2005). It is also supported by (Tran et al, 2014) when they found that external business characteristics were critical factors affecting the institutionalization of e-procurement in construction industry in Vietnam. They confirmed the importance of meso-level environmental factor in e-commerce adoption, as market forces tend to be relatively specific to a given sector and industry.…”
Section: Discussionsupporting
confidence: 90%
“…Perceived social awareness of e-commerce was found to have significant impact on institutionalization but not on a decision of initial adoption of e-commerce in SMEs. The result is supported by empirical findings in other developing countries (Tran et al, 2014). This implies that information sharing culture, positive perception of the role of information, and positive attitudes toward IT and e-commerce by people will be critical for SMEs in implementing sophisticatedly e-commerce (Teo et al, 2009).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…IT adoption generally supports firms to achieve a better performance such as to gain market share, higher productivity, better product and services innovation, reliable customer-oriented position and improved response to market changes (Cardona, Kretschmer, and Strobel, 2013;Hall, Lotti, and Mairesse, 2013;Tran et al, 2014). Adopting a new technology is only vital if it really improves the performance of business organisations (Yunis, Tarhini, and Kassar, 2018).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…In the context of Vietnam, some research (Tran, Zhang, Sun, & Huang, 2014;Han, Nguyen, & Nguyen, 2016) had been conducted to investigate issues related to electronic commerce and mobile commerce. Nonetheless, studies focusing on C2C in general and SMB C2C in particular are still lacking.…”
Section: C2c Business On Social Mediamentioning
confidence: 99%